Effectiveness of land use and density control measures in the city core area, Hyderabad, Pakistan - Masood, Mohammad; Kammeier, Hans Detlef; Archer, R.W.; Sheng, Yap Kioe; Norwegian Agency for Development Co-operation (NORAD) (Bangkok : Asian Institute of Technology, 1993)
The study aims to evaluate the Density Control Measures applied in the Core Area of Hyderabad to help in ascertaining the effectiveness. The study was conducted as an attempt to find out whether the present regulations enforced are adequate and effectively implemented and to pinpoint the gaps, major issues of divergence and the enforcement problems. It was identified that the problem is not only violations of the present regulations. But the actual problems are the inadequate and unsoundness of the applicable building regulations and the wide spread gaps due to a complex legal enforcement situation. The other reason was the non-coordination among different departments within Hyderabad Development Authority. In the light of such findings, several recommendations are formulated to improve the legal and technical issues. The proposals include, a separate set of regulations should be formulated for the Core Area of Hyderabad, after considering the practical conditions prevailing in the area like plot sizes, socioeconomic conditions of the people and the future trend of vertical and horizontal expansion.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1993
Keywords: Land use -- Pakistan -- Hyderabad